2018
DOI: 10.1371/journal.pone.0208874
|View full text |Cite
|
Sign up to set email alerts
|

Assessing sound symbolism: Investigating phonetic forms, visual shapes and letter fonts in an implicit bouba-kiki experimental paradigm

Abstract: Classically, in the bouba-kiki association task, a subject is asked to find the best association between one of two shapes–a round one and a spiky one–and one of two pseudowords–bouba and kiki. Numerous studies report that spiky shapes are associated with kiki, and round shapes with bouba. This task is likely the most prevalent in the study of non-conventional relationships between linguistic forms and meanings, also known as sound symbolism. However, associative tasks are explicit in the sense that they highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Cuskley and colleagues reported that written pseudowords with written round letters were associated with round figures, while pseudowords with spikey letters were associated with spiky figures [ 15 ]. Another study showed that written angular letters in spiky shapes as frames facilitated response times in a lexical decision task [ 16 ]. These previous findings suggest that visual properties of linguistic features (e.g., visual characteristics of letters and font styles) could be congruent with the visual properties of figures as referents (spiky or round figures [ 15 ]) or background (e.g., frames [ 16 ]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cuskley and colleagues reported that written pseudowords with written round letters were associated with round figures, while pseudowords with spikey letters were associated with spiky figures [ 15 ]. Another study showed that written angular letters in spiky shapes as frames facilitated response times in a lexical decision task [ 16 ]. These previous findings suggest that visual properties of linguistic features (e.g., visual characteristics of letters and font styles) could be congruent with the visual properties of figures as referents (spiky or round figures [ 15 ]) or background (e.g., frames [ 16 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that written angular letters in spiky shapes as frames facilitated response times in a lexical decision task [ 16 ]. These previous findings suggest that visual properties of linguistic features (e.g., visual characteristics of letters and font styles) could be congruent with the visual properties of figures as referents (spiky or round figures [ 15 ]) or background (e.g., frames [ 16 ]). In this study, we used written Japanese sound-symbolic words which included long vowels (e.g., フーフー , fuufuu ) and short vowels (e.g., フフ , fufu ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there is some evidence of this in the literature (see [7, 63, 64]; cf. [66]). It may be that round shape sound symbolism overwhelmed any effects of grammatical gender, but that sharp shape sound symbolism did not.…”
Section: Discussionmentioning
confidence: 99%
“…Cuskley et al (2017) showed that both spoken and written pseudowords (e.g., gege) orthographically associate with meaningless figures (e.g., a round shape). Another study also found that participants quickly matched spiky frames with angular fonts (De Carolis et al, 2018). These findings suggest that while sound symbolism is not an illusion that would actually be explained by purely visual phenomena involving the shape of letters (especially since sound symbolism occurs in human communities who do not have a written system for their languages), the visual shape of written stimuli might lead to additional effects that might partially blur sound symbolic associations.…”
Section: Introductionmentioning
confidence: 92%